RESEARCH OF DETERMINANTS OF NON-PERFORMING LOANS OF THE BANKING SECTOR OF SERBIA - Milišić, Nela; Račić, Željko (International Journal of Economic Practice and Policy, 2020)
The aim of this paper is to identify and analyze important internal and macroeconomic factors that determine the level of non-performing loans in the domestic banking sector thus contributing to the process of managing banks’ credit risk. The research is based on the application of linear regression model (OLS). In accordance with the results, we have concluded that the growth in lending activities and the concentration of the five largest banks contributed to the increase in the share of non-performing loans in the credit portfolio of the banking sector.